2007
DOI: 10.1890/06-2037.1
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Pond-Breeding Amphibians to Wildfire: Short-Term Patterns in Occupancy and Colonization

Abstract: Abstract. Wildland fires are expected to become more frequent and severe in many ecosystems, potentially posing a threat to many sensitive species. We evaluated the effects of a large, stand-replacement wildfire on three species of pond-breeding amphibians by estimating changes in occupancy of breeding sites during the three years before and after the fire burned 42 of 83 previously surveyed wetlands. Annual occupancy and colonization for each species was estimated using recently developed models that incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 51 publications
3
43
0
Order By: Relevance
“…Thus, we predict that other species requiring early successional or open habitats for reproduction (e.g., chorus frogs, narrow-mouthed toads, spadefoot toads) would benefit from the presence of breeding pools in clearcuts (e.g., use of skidder ruts; Cromer et al 2002). Hossack and Corn (2007) reported that disturbance created by wildfire can also benefit some pond-breeding amphibians, especially if fire creates or mimics early successional habitats. This does not mean that all stages of these species would benefit from clearcut or early successional habitat.…”
Section: Ecological Consequences and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we predict that other species requiring early successional or open habitats for reproduction (e.g., chorus frogs, narrow-mouthed toads, spadefoot toads) would benefit from the presence of breeding pools in clearcuts (e.g., use of skidder ruts; Cromer et al 2002). Hossack and Corn (2007) reported that disturbance created by wildfire can also benefit some pond-breeding amphibians, especially if fire creates or mimics early successional habitats. This does not mean that all stages of these species would benefit from clearcut or early successional habitat.…”
Section: Ecological Consequences and Mechanismsmentioning
confidence: 99%
“…Thus, the larval aquatic stage presumably benefits from the presence of pools in small clearcuts, but juvenile and adult treefrogs must find suitable forested habitat nearby (Johnson et al 2007. Hossack and Corn (2007) found that toads (Bufo boreas) increased the use of wetlands up to two to three years after wildfires, and suggested that this species was adapted to disturbance created by fire. However, some species, such as the wood frog in Maine, benefited little from breeding pools in clearcuts; these most likely represent species with a strongly forest-dependent life history (Blomquist and Hunter 2009).…”
Section: Ecological Consequences and Mechanismsmentioning
confidence: 99%
“…Habitat management for amphibians includes creating or restoring breeding ponds, increasing the connectivity between ponds, and establishing and maintaining shallow open water habitats by grazing or fire management (Bisson et al 2003;Hazell et al 2004;Pilliod et al 2003). Although there is a growing body of knowledge on how controlled and natural fires affect amphibian communities, the issue is far from settled due to the complexity of species-specific effects that depend on the local habitat structure and populations (Hossack and Corn 2007). Short-term negative effects include increased solar and UV-B radiation, high surface temperatures, aridification, and increased predation (Pilliod et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite high management and policy interest in wildlife, faunal response to fire has received substantially less attention. Much of this is due to the difficulty of studying fire-wildlife interactions; consequently, a great deal of the literature is based upon convenience sampling of wildfires that burned preexisting sample points (e.g., Smucker et al 2005, Hossack and Corn 2007, Kotliar et al 2007. Reviewing global fire literature on the birds, the best-studied vertebrate taxon, Leidolf and Bissonette (2009) found just over 500 documents, of which ,50% were journal articles containing original research and of which .50% had been published since 1990.…”
Section: Introductionmentioning
confidence: 99%